2009
DOI: 10.1016/s1607-551x(09)70528-5
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Behavioral Parent Therapy in Preschool Children With Attention‐Deficit Hyperactivity Disorder

Abstract: The purpose of this study was to assess the effectiveness of a behavioral parent therapy (BPT) program in children with attention-deficit hyperactivity disorder (ADHD) using multidimensional evaluations, the Child Behavior Checklist (CBCL) and the Teacher Report Form (TRF). Between 2001 and 2005, the parents of 21 preschool children with ADHD were divided into six groups and participated in a series of 11 BPT sessions. Before and after BPT, the parents completed the CBCL, and the teachers completed the TRF. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
1
1
0
5
Order By: Relevance
“…Previous studies that focused on the efficacy of behaviour training programs have not reported findings consistent with the results of this study 15,32. That is, teachers perceive fewer benefits with regard to the children's behavioural symptoms than did parents.…”
Section: Discussionsupporting
confidence: 54%
“…Previous studies that focused on the efficacy of behaviour training programs have not reported findings consistent with the results of this study 15,32. That is, teachers perceive fewer benefits with regard to the children's behavioural symptoms than did parents.…”
Section: Discussionsupporting
confidence: 54%
“…Hay diez ECA de calidad alta y media sobre los diferentes tipos de programas utilizados [205][206][207][208][209][210][211][212][213][214] . Además se identificaron siete ensayos clínicos de calidad baja [215][216][217][218][219][220][221] y un estudio observacional 222 .…”
Section: Connect Parent Group (Cpg)unclassified
“…Hasil yang didapatkan mendukung beberapa penelitian serupa yang telah dilakukan sebelumnya. Beberapa contohnya adalah penelitian dari Huang (2009) dan Chacko (2006). Hasil penelitian Huang (2009) membuktikan bahwa BPT efektif untuk menurunkan stres pengasuhan pada populasi ibu yang memiliki anak dengan ADHD di usia pra-sekolah.…”
Section: Tabel 2 Data Deskriptif Kelompok Eksperimen Dan Kontrolunclassified
“…Beberapa contohnya adalah penelitian dari Huang (2009) dan Chacko (2006). Hasil penelitian Huang (2009) membuktikan bahwa BPT efektif untuk menurunkan stres pengasuhan pada populasi ibu yang memiliki anak dengan ADHD di usia pra-sekolah. Hasil penelitian Chacko (2006) membuktikan efektivitas modif ikasi BPT pada populasi ibu yang memiliki anak dengan ADHD.…”
Section: Tabel 2 Data Deskriptif Kelompok Eksperimen Dan Kontrolunclassified